The impact of worker effort on public sentiment towards temporary migrants - Gil S. Epstein; Alessandra Venturini (Bar-Ilan University, Department of Economics, 2011)
Temporary and circular migration programs have been devised by many destination countries and supported by the European Commission as a policy to reduce welfare and social costs of immigration in destination countries. In this paper we present an additional reason for proposing temporary migration policies based on the characteristics of the foreign labor-effort supply. The level of effort exerted by migrants, which decreases over their duration in the host country, positively affects production, real wages and capital owners' profits. We show that the acceptance of job offers by migrants result in the displacement in employment of national workers. However it increases the workers' exertion, decreases prices and thus can counter anti-immigrant voter sentiment. Therefore, the favorable sentiment of the capital owners and the local population towards migrants may rise when temporary migration policies are adopted.
Keywords: 330; Migration; Exertion of effort; Contracted Temporary Migration; Saisonarbeitskräfte; Arbeitsmigranten; Arbeitsmigranten; Arbeitsleistung; Öffentliche Meinung; Ethnische Diskriminierung; Theorie